Helmet CPAP treatment in patients with COVID-19 pneumonia: a multicentre cohort study - Aliberti, Stefano (Eur Respir J, 2020)
Helmet CPAP treatment fails in up to 44% of patients with moderate-to-severe hypoxaemic acute respiratory failure due to COVID-19 pneumonia https://bit.ly/3g7FAB8